ROLE OF BIOCHAR AND BENTONITE IN IMPROVING SOME CHEMICAL PROPERTIES OF DESERT SOIL, GROWTH AND YIELD OF BROAD BEAN (Vicia faba L.) - Saja. H. W. Al-Mishyyikh; Abbas. K. A. Jarallah (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
A field experiment was conducted to evaluate effect of some soil amendments (biochar and bentointe) in some chemical properties, growth and yield of broad bean in desert soil. The study included four levels of biochar (0, 10, 20 and 30 Mg ha-1 and Four levels of bentonite (0, 10,20 and 30 Mg ha-1) . Randomized complete block design (RCBD) with three replicates were used. The results showed that the application of biochar and bentonite significantly affected all the soil chemical properties under study and plant parameters.  The level 15 Mg ha-1 of biochar  gave the lowest valuesreached 7.30 and 3.57 dS m-1 for soil pH  and EC and gave highest  values reached 51.93 g kg-1 soil  and 19.13 C mol+kg-1 soil  for O.M and CEC and the highest valuesin plant height , leaf area,  dry weight of vegetative part and fresh pods yield were 56.3 cm, 3028.6 cm2 plant-1, 81.53 g plant-1 and 17.540 Mg ha-1,  respectively.  The results showed also that the level 30 Mg ha-1 of bentonite gave the highest values were 7.45, 4.48 dS m-1, 34.48 g kg-1 and 18.69C mol+kg-1 soil for pH, EC, O.M and CEC respectively while the highest values of plant parametersreached 56.9 cm, 3085.9 cm2 plant-1, 79.25 g plant-1  and 18.99030 Mg ha-1 for plant height , leaf area, dry weight of vegetative part and fresh pods yield, respectively. As for the interaction, the treatment (15 Mg ha-1biochar, 0 Mg ha-1 bentonite) achieved the lowest value for pH and EC reaching 7.08 and 3.13 dS m-1respectively while the treatment (15 Mg ha-1biochar, 30 Mg ha-1 bentonite) achieved the highest value for O.M, CEC and plant parameters under study.